Determining Hybridization in Jack Pine and Lodgepole Pine from British Columbia - Wood, Lisa J.; Hartley, Ian D.; Watson, Paul (SWST, 2009)
This study was conducted to find wood quality evidence of hybridization between jack pine (Pinus banksiana) and lodgepole pine (Pinus contorta var. latifolia) in northeast British Columbia (BC). To determine if wood and fiber traits could be used as distinguishing features among jack pine, lodgepole pine, and their hybrids, differences in morphology and wood and fiber traits were related to the genetic identity of each sample. Thirty samples each of pure lodgepole pine, pure jack pine, and potential hybrids were collected from the Prince George area of BC, the Smoky Lake area of Alberta, and the Fort Nelson region of BC, respectively. Two 10-mm cores (bark to bark) were taken from each tree and analyzed for fiber length and coarseness, microfibril angle (MFA), basic density, earlywood:latewood ratios, and cell dimensions. Needle and cone morphology was used to distinguish among species groups in the field. Based on genetically identified samples, the fiber traits that best differentiated among pure jack pine, lodgepole pine, and hybrids were MFA and cell area.